2013
DOI: 10.1002/oby.20235
|View full text |Cite
|
Sign up to set email alerts
|

Metformin modifies the exercise training effects on risk factors for cardiovascular disease in impaired glucose tolerant adults

Abstract: Impaired glucose tolerant (IGT) adults are at elevated risk for cardiovascular disease (CVD). Exercise or metformin reduce CVD risk, but the efficacy of combining treatments is unclear. To determine the effects of exercise training plus metformin, compared to each treatment alone, on CVD risk factors in IGT adults. Subjects were assigned to: placebo (P), metformin (M), exercise plus placebo (EP), or exercise plus metformin (EM) (8/group). In a double-blind design, P or 2000mg/d of M were administered for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 42 publications
6
38
2
1
Order By: Relevance
“…Nevertheless, it has been demonstrated that antidiabetic medication can influence training‐induced adaptations. Metformin, for example, can attenuate some of the effects of exercise training on cardiovascular risk factors . However, medication intake among subjects from both groups was quite similar in the present study.…”
Section: Discussioncontrasting
confidence: 40%
“…Nevertheless, it has been demonstrated that antidiabetic medication can influence training‐induced adaptations. Metformin, for example, can attenuate some of the effects of exercise training on cardiovascular risk factors . However, medication intake among subjects from both groups was quite similar in the present study.…”
Section: Discussioncontrasting
confidence: 40%
“…This same investigation demonstrated that metformin use blunted some of the beneficial effects of the combined training related to a reduction in cardiovascular disease risk such as systolic blood pressure or high sensitivity C-reactive protein (hs-CRP) [70]. These findings conflict with an earlier investigation in insulin-resistant individuals in which two to three weeks of metformin treatment blunted the effects of a single bout of ET on insulin sensitivity [71].…”
Section: Chronic Resistance Training and Medication Usementioning
confidence: 99%
“…Regarding beneficial effects on the cardiovascular system, metformin administration and exercise in humans have been shown to lower systolic and diastolic blood pressure (118); however, the combination was not more effective (132).…”
Section: Fasting/food Withdrawal Endurance Exercise and Interventiomentioning
confidence: 99%